2021
DOI: 10.3390/ijms22158338
|View full text |Cite
|
Sign up to set email alerts
|

The Prion-Like Spreading of Alpha-Synuclein in Parkinson’s Disease: Update on Models and Hypotheses

Abstract: The pathological aggregation of the presynaptic protein α-synuclein (α-syn) and propagation through synaptically coupled neuroanatomical tracts is increasingly thought to underlie the pathophysiological progression of Parkinson’s disease (PD) and related synucleinopathies. Although the precise molecular mechanisms responsible for the spreading of pathological α-syn accumulation in the CNS are not fully understood, growing evidence suggests that de novo α-syn misfolding and/or neuronal internalization of aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 261 publications
(384 reference statements)
0
52
0
Order By: Relevance
“…The appearance of multiple distinct conformation α-syn fibrils under identical conditions may also be one of the steps in the complex mechanism of pathogenesis in Parkinson's disease and other synucleinopathies. Currently, the exact mode of alpha-synuclein-related disorder onset and propagation is not fully known, with multiple possible mechanisms proposed, such as prion-like spreading [38] and trans-synaptic α-syn propagation [39,40]. It has also recently been shown by Ferreira et al [41] and Peng et al [42] that certain α-syn fibril types have a considerably higher neurodegenerative potential than others.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of multiple distinct conformation α-syn fibrils under identical conditions may also be one of the steps in the complex mechanism of pathogenesis in Parkinson's disease and other synucleinopathies. Currently, the exact mode of alpha-synuclein-related disorder onset and propagation is not fully known, with multiple possible mechanisms proposed, such as prion-like spreading [38] and trans-synaptic α-syn propagation [39,40]. It has also recently been shown by Ferreira et al [41] and Peng et al [42] that certain α-syn fibril types have a considerably higher neurodegenerative potential than others.…”
Section: Discussionmentioning
confidence: 99%
“…The self-aggregation of α-syn promotes membrane disruption, which can result from the formation of an amphipathic helical structure of α-syn [ 6 ]. Modern views of PD encompass the cell-to-cell trans-synaptic spread of α-syn [ 25 , 26 ] and the existence of many α-syn polymorphs that might be responsible for different synucleinopathies [ 27 , 28 ]. The cell membrane containing integrins is thought to play an important role in the intercellular synaptic diffusion of α-syn.…”
Section: Discussionmentioning
confidence: 99%
“…Intraneuronal αSyn aggregates are triggered by internalized small fibers that do not contact membranes directly, suggesting that this mechanism is relevant to the spreading of aggregated pathologies [76]. Although the molecular mechanisms responsible for spreading pathologic αSyn are poorly understood, a growing body of evidence indicates that de novo misfolding and/or neuronal internalization of aggregated αSyn facilitates conformational templating of endogenous αSyn monomers in a prion-like manner [77]. Recent studies demonstrating that cellular prion protein (PrP C ) mediates αSyn uptake, localization, and toxicity in vitro and in vivo confirmed previous results which showed that PrP C internalizes soluble misfolded αSyn, indicating its important role in its internalization required for the intercellular spread of αSyn [78].…”
Section: Self-propagation Of Prionoidsmentioning
confidence: 99%